Analisis Profit Margin, Return On Asset, dan Return On Equity dalam Mengukur Kinerja Perusahaan PT. Kino Indonesia (Periode 2020-2022) - Pina Anggraeni; R. Nasution (STIE PGRI Dewantara Jombang, 2024)
This study aims to aims to determine the financial performance of the company PT Kino Indonesia Tbk with profit margin, return on assets, and return on equity (profitability ratios) which are the research indicators. The research was conducted at PT Kino Indonesia, which is experiencing losses in 2022 due to the post-pandemic, data obtained from the Indonesia Stock Exchange in the form of annual financial reports from 2020 to 2022. The data analysis used is descriptive statistical analysis technique. The results of this study indicate that (1) the company's profit margin is not good enough. Because in 2022 the company suffers a loss. (2) the company's ROA is not good, because the company has not been able to manage its assets effectively. (3) the company's ROE is not good, because the ROA value is far below the standard ratio value. This shows that the company is not good enough in managing the company's finances during the post-pandemic period.